THE ACCURACY TEST OF TECHNICAL ANALYSIS OF MOVING AVERAGE, BOLLINGER BANDS, AND RELATIVE STRENGTH INDEX ON STOCK PRICES OF COMPANIES LISTED IN INDEX LQ45 - Daniswara, Dipta Amelia; Widjanarko, Hendro; Hikmah, Khoirul (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2022)
This study aims to test and provide empirical evidence of the accuracy of the technical analysis indicators Moving Average, Bollinger Bands, and Relative Strength Index in predicting the direction of stock price movements. This research focuses on stocks that represent the Indonesian stock Market, namely the LQ45 stock index for the period February 2021 - July 2021. Data were collected through the tradingview.com platform. To test the research hypothesis, the statistical differences between the predictions and the reality of stock price movement were tested using Mann-Whitney non-parametric test. The results of this study found that there was no difference between the predictions of the direction of stock price movements produced by the three indicators and the actual prices, which means that the three indicators are accurate. From the results of the analysis and comparison of the performance of the three indicators from the number of signals, the average rate of return, and the sample observations, it can be concluded that the Relative Strength Index indicator has a more optimal accuracy performance compared to the other two indicators. indicator. The results of this study can be used as a reference for capital market investors in choosing technical analysis methods that can help make more appropriate investment decisions.